The Efficacy of the Yasmin[Ethinylestradiol-Drospirenone (0.03/3 mg)] Treatment for Postoperative Abortion: A Protocol of Meta-Analysis - Tian, Tian; Feng, Huiyan; Liao, Xiaoqian; Su, Qiling; Li, Yunhui; Li, Xiaomao (Frontiers in Medicine, 2022)
Background: Induced abortion is a universal phenomenon and about 25% of pregnancies in the world end in induced abortion. Induced abortion refers to the use of artificial or drug methods to terminate the pregnancy in the early stage of pregnancy, which is a remedy for failed contraception and accidental pregnancy. Induced abortion means surgical abortion. There are two commonly used methods: negative pressure suction abortion and forceps curettage for induced abortion. Abortion is invasive and it will cause great harm to women's reproductive function. Clinically, there are also cases of re-pregnancy within 3 months after abortion or even re-pregnancy without recovery of menstruation. To improve symptoms and reduce these complications, antibiotics, motherwort, and Yasmin are clinically used alone or in combination after induced abortion. Methods: Data were collected from six databases, including three English databases of Cochrane Library, PubMed and Embase, and three Chinese databases of CNKI, Wanfang, and Weipu. The original indicators of vaginal bleeding, menstrual recovery time, bleeding time, endometrial thickness, and so on in 21 days after surgery were included, and the incidence of postoperative bleeding less than menstrual volume, menstrual re-fluid time ≤ 37 days, bleeding time ≤ 7 days, re-pregnancy without menstruation, re-pregnancy within 3 months after the operation. Review Manager5.4 software was downloaded from the Cochrane website to evaluate the quality of the literature and analyze the results using random or fixed-effects models. The outcome of index data is divided into two types, one is dichotomy, and the other is measurement data. The binary data is expressed by odds ratio (OR), and the measurement data is expressed by mean difference (MD), and the confidence interval of both is 95% ( 95% CI). Results: After completing this meta-analysis, the results will be available. Conclusion: This study is a systematic analysis of the use-value of Yosamin (Drospirenone Ethinylestradiol tablets) combined with antibiotics and Leonurus in postoperative induced abortion. The results will provide reliable data basis for the value of Yosamin combined with antibiotics and Motherwort in postoperative induced abortion. Abbreviations: CI=confidence interval, OR=odds ratio, MD=average difference, RCT=randomized controlled trial PROSPERO registration number: CRD42021246764